Sustainability and strategic management accounting: evidence of green manufacturing in Thailand - Worakorn Pumiviset; Muttanachai Suttipun (Cogent Business & Management, 2024)
This study aims to investigate the effects of Strategic Management Accounting (SMA) on sustainable performance consisting of economic, environmental, and social performance. A questionnaire was utilized to collect primary data through a survey approach. This study includes as samples 187 green manufacturing companies in Thailand with green industry certifications from the Department of Industrial Works of Thailand. The statistical software was applied to implement the structural equation model. The results show that the causal relationship model fit to the empirical data was at an acceptable level. SMA has a significant positive direct effect on economic, environmental, and social performance. Moreover, environmental and social performance act in a partial mediating role in the relationship between SMA and economic performance. The findings also reveal that the three components of sustainable performance have causal relationships. In dealing with dynamic changes in the business environment, decision-making based on SMA information can be more proactive. The implementation and adoption of SMA techniques are known to be limited in emerging economies, with little information available on adoption and integration. The results of previous investigation are also inconclusive.
Keywords: 650; Strategic management accounting; sustainable performance; green manufacturing; Thailand